The Influence of Mathematical Representation Ability on Students' Mathematical Communication Skills - Nurma Izzati; Reva Salma Adhany (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Mathematical communication skills and mathematical representation skills are two important skills in mathematics learning. However, students' mathematical communication skills remain relatively low, so a study is needed to identify the factors that affect them, including mathematical representation ability. This study aims to examine the influence of mathematical representation skills on students' mathematical communication skills in grade VII C at SMP Al Washliyah Sumber. This study uses a quantitative approach with an explanatory correlational design and simple linear regression. The research sample consisted of 31 students selected through purposive sampling. The research instrument is in the form of a description test developed based on indicators of mathematical representation ability and mathematical communication ability, which have met the criteria for validity and reliability. The study's results show that mathematical representation ability has a positive, significant effect on students' mathematical communication skills. These findings suggest that students with good mathematical representation skills tend to have better mathematical communication skills. This research suggests that mathematics learning should facilitate the use of various forms of mathematical representation to improve students' mathematical communication skills.